The Role of digital leadership, work enggament and compensation on work performance of SMEs - Purnomo, D (AGUSPATI Research Institute, 2024)
The purpose of this study is to analyze the relationship between digital leadership variables and employee performance, analyze the relationship between compensation variables and employee performance, analyze the relationship between Employee Empowerment variables and employee performance. This research method is quantitative. Population and Sample In this study, the sampling used was purposive sampling. Data Analysis Technique In this study, the data that has been processed and analyzed will be used for the analysis design, in this study the data analysis used smart-PLS software version 3. The respondents of this study were 346 SME managers in Indonesia. The measurement model with reflective and formative indicators was used in the study, where the validity and reliability were tested. In running the PLS algorithm in smart-PLS, an external model estimate was obtained by producing convergent validity values, discriminant validity, AVE, Cronbach's alpha and composite reliability. The research data were obtained by distributing online questionnaires, the questionnaire was designed to contain statement items using a Likert scale of 1 to 7. The collected data will be analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) methodology. SEM-PLS was chosen because of its ability to handle complex models and smaller sample sizes, making it well suited to the intricacies of this study. The analysis will be conducted in several stages: Measurement Model Assessment: Confirmatory factor analysis will be used to validate the measurement model and ensure the reliability and validity of the latent variables. Structural Model Estimation: The structural relationships between organizational culture, innovative leadership, digital technology adoption, and startup success will be examined using SEM-PLS. Bootstrapping: To increase the robustness of the results, bootstrapping with resampling will be used to assess the significance of the path coefficients and test the overall model fit. The results of this study's analysis are that there is a positive effect of digital leadership on employee performance, there is a positive effect of compensation on employee performance, there is a positive effect of employee empowerment on employee performance